Philosophical Hermeneutics on Culture for Sustainable Develop - Ifeanyichukwu Ogbodo, Ignatius; Ohabuenyi Abah, George (International Journal of Psychosocial Rehabilitation, 2021)
In recent times, the world has witnessed rising clashes among cultures or peoples of different cultural orientations. It has been observed that in most of the cases especially those that have developed into full scale wars, development have been seriously retarded. This paper examines the interface between philosophical hermeneutics culture and religion with a view to assessing whether philosophical hermeneutics on culture can lead to sustainable development. Philosophy promises to create a suitable characterisation of the relationship between culture and religion. This paper adopts hermeneutical, expository and textual analytical methods. This paper argues that philosophical interpretative approach to culture and religion can move the society in the direction of sustainable development.